2005
DOI: 10.1063/1.2139620
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the superlens: Manipulating geometry to enhance the resolution

Abstract: We analyze the performance of a planar lens based on realistic negative index material in a generalized geometry. We demonstrate that the conventional superlens design (where the lens is centered between the object and the image) is not optimal from the resolution point-of-view, develop an analytical expression for the resolution limit of a generalized lens, use it to find the optimum lens configuration, and calculate the maximum absorption practical nearfield superlenses may have. We demonstrate that in contr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 29 publications
1
37
0
1
Order By: Relevance
“…[5][6][7] Absorption is one of the largest problems that needs to be addressed to enable applications of NIMs. 8,9 A transfer of the near-field image into the SH frequency domain, where absorption is typically much less, was proposed in Refs. 10 and 11 as a means to overcome dissipative losses and thus enable the NIM-based superlens.…”
mentioning
confidence: 99%
“…[5][6][7] Absorption is one of the largest problems that needs to be addressed to enable applications of NIMs. 8,9 A transfer of the near-field image into the SH frequency domain, where absorption is typically much less, was proposed in Refs. 10 and 11 as a means to overcome dissipative losses and thus enable the NIM-based superlens.…”
mentioning
confidence: 99%
“…Both for the quasistatic case [3] and for the full time harmonic Maxwell equations [17,18] it was shown that contrary to the conventional explanation where the field intensity has a minimum at the front interface of the lens, the field actually diverges to infinity in two anomalously resonant layers of width 2(d − d 0 ), one centered on the front interface and one centered on the back interface. Indications of large fields in front of the lens [16,19,20,21,22] were followed by definitive numerical evidence of enormous fields [23]. When d 0 < d/2 the resonant layers interfere with the source.…”
Section: Introductionmentioning
confidence: 99%
“…It includes the resonant contribution of surface modes with a finite in-plane wave vector k y and in the limit ǫ → −1, |k y | >> ω/c it is reduced to that obtained in Ref. [7] where the authors investigated the resolution limit of the slab of "negative" material with dielectric permittivity ǫ = −1 + iǫ ′′ and magnetic permeability µ = −1 + iµ ′′ . It should also be noted that the location (in k y wave vector space) of the two resonances not only depends on the absolute value of the dielectric constant ǫ but also the thickness of the slab d. For a very thin slab, the two resonances are separated (smaller slab thicknesses result in greater peak separation in k y space).…”
Section: Interference Of the Evanescent Waves And Effect Of Supermentioning
confidence: 99%
“…The increased interest in properties of such media has been driven by their potential applications in various branches of science and technology. One possible application is related to the possibility of creating the so called superlens: a subwavelength optical imaging system without the diffraction limit [4,5,6,7]. The superlens phenomenon is essentially based on amplification of evanescent waves, facilitated by the excitation of the surface plasmons [6].…”
Section: Introductionmentioning
confidence: 99%